ISOLASI DAN IDENFIKASI BAKTERI SALMONELLA DAN Staphylococus aureus PADA IKAN TONGKOL ASAP YANG DISIMPAN PADA SUHU DAN LAMA PENYIMPANAN YANG BERBEDA - Abdul Majid; Nikmah Majid (CHMK Applied Science Journal, 2021)
ABSTRACT This research aimed to know the isolation and identification of Salmonella and Staphylococcus aureus bacterium content of smoked at Euthynnus afinis of temperature and duration of storage. This research represent research of laboratoris eksperimental with factorial experiment desain 2 factor, that is A factor treatment of temperature ( 0oC, 4oC, 25oC), and duration of storage treatment factor ( 0, 4, 8, 12 day) each treating 3 replikasi. The result of isolation and identification no Salmonella were found, howefer Staphylococcus aureus were found. The total Staphylocuccus aureus bacterium content of smoked Euthynnus afinis: Treatment of temperature 4oC, and duration of storage 12 and 16 day, mean of colony 3,5 x 104 CFU/ml, and 2,2 x 105 CFU/ml. Treatment of temperature 25oC, and duration of storage 4, 8, 12 and 16 day, each mean of colony 1,6 x 104 CFU/ml, 2,7 x 104 CFU/ml, 1,6 x 105 CFU/ml, dan 4,2 x 105 CFU/ml. Keywords: Isolation, Identification, Salmonella, Sataphylococcusaur eureus, Euthynnus afinis